Identification of intrinsic mechanisms and controlling factors for γ′ rafting of Ni-based single crystal superalloys - Yongmei Li; Zihao Tan; Xinguang Wang; Yanfei Liu; Jide Liu; Jinlai Liu; Jinguo Li; Xiaofeng Sun; Yizhou Zhou (Materials Research Letters, 2025)
The present study elucidated the formation mechanism of γ′ rafting related to dislocation motion and clarified that γ′ rafting could be divided into the mismatch-driven stage I and diffusion-controlled stage II. This transition arose from the dual effects of dislocations: relaxing lattice mismatch and boosting elements diffusion. In detail, once the elastic misfit stress was nearly released by forming dense dislocation networks, the effective bulk diffusivity and the mobility of matrix dislocations would control the subsequent γ′ rafting. This study offered insights into the rafting of γ′ phase and proposed valuable suggestions to improve the microstructural stability of Ni-based single crystal superalloys.